Organising white-collar and corporate crimes - Lord, Nicholas; Levi, Michael (Routledge, 2025)
"This book explores how we can re-constitute our approach to analysing and empirically investigating the organisation of white-collar and corporate crimes, with a view to building fuller theoretical and empirical accounts. The work demonstrates how knowledge can be produced and systematised within a conceptual and analytical framework concerned with understanding how such crimes are organised, why they are organised as they are, who gets involved in them as primary offenders and as facilitators, and the 'real' factors that shape these organisational dynamics over time within particular contexts and under varying conditions. In doing so, the volume examines the distal (far-off) and proximal (close) social arrangements and relations that create and shape emergent white-collar crime opportunities and their structures. It also investigates the mechanisms, relationships, processes and conditions that are necessary for the commission, or the unfolding, of white-collar crimes, or for their non-commission. How these are contingently connected to particular contexts is explored. The work also considers the people who collaborate, connect and otherwise associate, whether ephemerally or for longer periods, in the pursuit of criminal goals, and the actual or potential skills, expertise and abilities of these people to accomplish or resist particular behaviours that are required of them. Finally, the volume assesses the human, social, cultural and material antecedents that enable white-collar crimes to flourish or fade. The work will be of particular interest to scholars theorising about and empirically investigating white-collar and corporate crimes, or seeking to understand empirical approaches to analysing such behaviours and other types of crime. As such, it is primarily aimed at critical social scientists, including criminologists and sociologists, as well as socio-legal, business, economics, and political studies scholars. The work will also be of interest to practitioners and policymakers keen to learn more about how and why these crimes are organised as they are"-- Provided by publisher.
Keywords: Commercial crimes -- Law and legislation.; White collar crimes -- Law and legislation.; Corporations -- Corrupt practices.; elektronické knihy; electronic books